Meningkatkan Keterampilan Menendang Bola pada Permainan Sepakbola melalui Modifikasi Alat Bantu Bola Pelastik pada Murid Kelas V SD Inpres Panggentungan Utara Kabupaten Gowa - Achmad Karim; Ikadarny Ikadarny (Universitas PGRI Semarang, 2020)
Improving Kicking Ball Skills in Soccer Games through Modification of Plastic Ball Aids in Class V Elementary School Students North Panggentungan Gowa RegencyThis study aims to describe the planning, action, reflection, observation and the application of the modification of ballistic aids in improving ball kicking skills in the soccer game for the fifth grader student of north panggentungan elementary school, Gowa Regency. This research is a Class Action Research (CAR) that conducted 3 times in cycle I and cycle II meetings. The data of this research is the skill of the research is the skill of kicking ball in soccer games. The source of the research data is the 5th grader students of the north panggentunagn elementary school in Gowa Regency. The collected data was analyzed deskriptive quantitatively. The result of the quantitative analysis of the kicking ball skill data showd that the number of students who completed in cycle I was 20 students with a percentage of 66,67% and the number of students who completed cycle II was 30 students with a percentage of 100%. Qualitative analysys result showed that there was a significant increasing in kicking ball skills at soccer games. Based on the results of the study, it can be concluded that the study, it can be concluded that the physical education learning through the midification of plastic ball aidscan improve ball kicking skills in soccer games for 5th grader students of north panggentungan elementary school, Gowa Regency.. Keywords: Kicking ball, Plastic ball, Kicking skill, Soccer, Modification Penelitian ini bertujuan mendeskripsikan perencanaan, tindakan, observasi refleksi dan penerapan Modifikasi alat bantu bola pelastik dalam Meningkatkan Keterampilan Menendang Bola pada Permainan Sepakbola Murid Kelas V SD Inpres Panggentungan Utara Kabupaten Gowa.Penelitian ini merupakan Penelitian Tindakan Kelas yang dilaksanakan sebanyak 3 kali Pertemuan Siklus I dan Siklus II. Data Penelitian ini adalah Keterampilan Menendang Bola pada Permainan Sepakbola. Sumber data Penelitian adalah Murid Kelas V SD Inpres Panggentungan Utara Kabupaten Gowa yang berjumlah 24 orang. Data yang terkumpul dianalisis secara Deskriptif Kuantitatif. Hasil analisis Kuantitatif data Keterampilan Menendang Bola menunjukkan bahwa jumlah Murid yang tuntas pada Siklus I adalah 20 orang dengan persentase 66,67% dan jumlah murid yang tuntas pada Siklus II adalah 30 orang dengan persentase 100%. Hasil analisis Kualitatif menunjukkan bahwa terdapat peningkatan Keterampilan Menendang Bola pada Permainan Sepakbola yang signifikan. Berdasarkan Hasil penelitian dapat disimpulkan bahwa pembelajaran penjas melalui Modifikasi alat bantu bola pelastik dapat Meningkatkan Keterampilan Menendang Bola pada Permainan Sepakbola Murid Kelas V SD Inpres Panggentungan Utara Kabupaten Gowa.Kata kunci: Menendang bola, Bola pelastik, Keterampilan menendang, Sepakbola, modifikasi